Associations Between State Laws Governing Recess Policy with Children's Physical Activity and Health. (9th March 2022) - Clevenger, Kimberly A.; Perna, Frank M.; Moser, Richard P.; Berrigan, David
Abstract: Background: State‐level laws governing recess policies vary widely across the United States. We characterize the presence of such laws and assess their associations with child‐level outcomes. Methods: The presence of a state recess law was determined using the Classification of Laws Associated with School Students (CLASS) database. Parents of 6‐ to 11‐year‐old children reported physical activity, overall health, school absences, school‐related problems, and ability to make/keep friends as part of the National Survey of Children's Health (NSCH). Logistic regression was used to compare outcomes in states with and without recess laws cross‐sectionally in 2018 and between 2003 and 2011/2012 using a difference‐in‐differences analysis. Results: In 2018, 20 states had a law recommending or requiring recess. Cross‐sectionally, the odds of being physically active every day (odds ratio, 95% confidence interval: 2.8, 1.2‐6.5) and having no difficulty making or keeping friends (2.9, 1.2‐7.2) were significantly higher for children residing in states with versus without a recess law. There were no significant associations in the difference‐in‐differences model. Conclusions: Significant cross‐sectional associations in 2018 were not confirmed by a difference‐in‐differences analysis of two waves of the NSCH. Short follow‐up time and the apparent weakness of existing state laws warrant further assessment of state‐level recess law.